Family cohesion, shame-proneness, expressive suppression, and adolescent mental health—A path model approach - van Eickels, Rahel L.; Tsarpalis-Fragkoulidis, Achilleas; Zemp, Martina (Frontiers in Psychology, 2022)
Objective: The family remains one of the most important relationship systems into early adulthood and provides an important foundation for lifelong mental health. Dysfunctional family cohesion can promote adjustment problems in adolescents and might also affect adolescents' self-concept and strategies for coping with emotional distress. To test these relationships and the underlying mechanisms, we proposed a dual mediation model describing the associations between family cohesion and internalizing and externalizing problems, mediated by shame-proneness and expressive suppression. Methods: A sample of 526 German-speaking adolescents aged 14 to 18 years from Austria, Germany, and Switzerland participated in an online self-report survey encompassing questionnaires on family cohesion, shame-proneness, expressive suppression, and psychological problems. We tested a path model to examine the indirect pathways of the associations between family cohesion and internalizing and externalizing problems via shame-proneness and expressive suppression, while controlling for age, gender, and guilt-proneness. Results: We found a significant dual mediation of the associations between family cohesion and internalizing and externalizing problems by shame-proneness and expressive suppression. The indirect pathways were all significant, except for the indirect pathway from family cohesion to externalizing problems via shame-proneness. Discussion: Our results provide a model for the mechanisms by which disrupted family cohesion can be related to psychological problems in adolescents. Expressive suppression emerged as crucial when considering the consequences of shame in adolescents, as vulnerability to shame was only indirectly related to externalizing problems via expressive suppression.